Anguilla rostrata - Angulo, Arturo (Zenodo, 2021)
Anguilla rostrata (Lesueur, 1817). American Eel; Anguila, Anguila de Mar, Anguila Verdadera, Anguila Americana. Distribution: Global: Western Atlantic Ocean; from southern Greenland to northwestern Venezuela; entering estuaries and littoral lagoons and ascending river courses; Costa Rica: LN, RF, SJ, SC, Sa, To, Pa, Ma and Si (Atlantic), 0– 20 m.a.s.l., Per, Dia (Cat). Occurrence and conservation status: Nat, EN. References: Bussing (1966: 236; brief description and information on distribution), Bussing (1998: 64; brief description, including illustrations and an identification key, information on distribution, with a map, and ecology), Angulo et al. (2013: 989; listed, including taxonomic information and distributional data) and Robertson & Van Tassell (2019: 2770; detailed description, including illustrations, information on distribution, with a map, and ecology). Published as part of Angulo, Arturo, 2021, New records and range extensions to the Costa Rican freshwater fish fauna, with an updated checklist, pp. 1-72 in Zootaxa 5083 (1) on page 21, DOI:10.11646/zootaxa.5083.1.1, http://zenodo.org/record/5800630